2012
DOI: 10.1007/s10162-012-0333-4
|View full text |Cite
|
Sign up to set email alerts
|

Monopolar Intracochlear Pulse Trains Selectively Activate the Inferior Colliculus

Abstract: Previous cochlear implant studies using isolated electrical stimulus pulses in animal models have reported that intracochlear monopolar stimulus configurations elicit broad extents of neuronal activation within the central auditory system-much broader than the activation patterns produced by bipolar electrode pairs or acoustic tones. However, psychophysical and speech reception studies that use sustained pulse trains do not show clear performance differences for monopolar versus bipolar configurations. To test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…They observed that the patterns produced by both stimuli at levels within a 5-dB range above their respective thresholds had comparable peak amplitudes and spreads of excitation. Similarly, Schoenecker et al (2012) equated their MP and BP stimuli so that they produced the same peak spike rate in inferior colliculus neurons and found similar tonotopic spreads of excitation for both configurations.…”
Section: Introductionmentioning
confidence: 90%
“…They observed that the patterns produced by both stimuli at levels within a 5-dB range above their respective thresholds had comparable peak amplitudes and spreads of excitation. Similarly, Schoenecker et al (2012) equated their MP and BP stimuli so that they produced the same peak spike rate in inferior colliculus neurons and found similar tonotopic spreads of excitation for both configurations.…”
Section: Introductionmentioning
confidence: 90%
“…It might be noted that later studies conducted at UCSF in a guinea pig model using the same electrode mapping strategy but applying a scala tympani-filling silicon rubber insert carrying the electrodes, again to 'ideally' locate stimulus contacts under the bony modiolus, recorded discrete monopolar stimulation-evoked response tuning that was equivalent to that achieved with bipolar stimulation (Schoenecker et al, 2012). The origin of these sharp differences with our studies in the 1970s and early 1980s is unclear.…”
Section: Addressing Issues Related To Controlling Patterns Of Auditormentioning
confidence: 84%
“…Don Eddington had already noted that interleaved pulsing could be used to minimize it. In studies largely led by Mark White, we had directly documented interference parametrically in both animal and human models (Merzenich et al, 1974b;Shannon, 1983a;White, 1978;Schoenecker et al, 2012;White, 1984;White et al, 1984)dand well understood the conditions for minimizing or avoiding it. Those and other observations led to our development, in 1984-86, of an initial model of an interleaved pulse-processor (IPP) CI model, designed to drive an 8-channel device, operating at rates up to about 600 Hz.…”
Section: Addressing Other Issues Related To Practical Questions Aboutmentioning
confidence: 97%
“…Smith and Delgutte (2007) reported essentially no difference in spatial selectivity between MP and BP configurations at the level of the inferior colliculus in cats when levels were lower than 5 dB above absolute threshold of neural activation. Also, Schoenecker et al (2012) reported that suprathreshold MP pulse trains can produce activation patterns that are at least as selective as BP pulse trains at the level of the inferior colliculus in cats and guinea pigs. While these two research studies serve to temper the belief that differences between electrode configurations are clearly demonstrated in animal studies, it is difficult to understand why such differences, when reported, are not easily demonstrable in humans.…”
Section: Discussionmentioning
confidence: 98%